Random‐Graft Polymer‐Directed Synthesis of Inorganic Mesostructures with Ultrathin Frameworks. Issue 20 (1st April 2014) - Jo, Changbum; Seo, Yongbeom; Cho, Kanghee; Kim, Jaeheon; Shin, Hye Sun; Lee, Munhee; Kim, Jeong‐Chul; Kim, Sang Ouk; Lee, Jeong Yong; Ihee, Hyotcherl; Ryoo, Ryong
Abstract: A widely employed route for synthesizing mesostructured materials is the use of surfactant micelles or amphiphilic block copolymers as structure‐directing agents. A versatile synthesis method is described for mesostructured materials composed of ultrathin inorganic frameworks using amorphous linear‐chain polymers functionalized with a random distribution of side groups that can participate in inorganic crystallization. Tight binding of the side groups with inorganic species enforces strain in the polymer backbones, limiting the crystallization to the ultrathin micellar scale. This method is demonstrated for a variety of materials, such as hierarchically nanoporous zeolites, their aluminophosphate analogue, TiO2 nanosheets of sub‐nanometer thickness, and mesoporous TiO2, SnO2, and ZrO2 . This polymer‐directed synthesis is expected to widen our accessibility to unexplored mesostructured materials in a simple and mass‐producible manner. Abstract : In the right direction : Mesostructured inorganic materials, such as zeolite nanosponge, TiO2 nanosheets, and nanosponges of TiO2, SnO2, and ZrO2 were synthesized using amorphous polymers as the structure‐directing agent. Many of these materials possessed quite uniform mesopores. Some of them even exhibited small‐angle X‐ray diffraction. The structure‐directing mechanism is also presented.